Emerging importance of molecular pathogenesis of vascular malformations in clinical practice and classifications. (August 2020) - Pang, Calver; Lim, Chung Sim; Brookes, Jocelyn; Tsui, Janice; Hamilton, George
Vascular malformations occur during early vascular development resulting in abnormally formed vessels that can manifest as arterial, venous, capillary or lymphatic lesions, or in combination, and include local tissue overdevelopment. Vascular malformations are largely caused by sporadic somatic gene mutations. This article aims to review and discuss current molecular signaling pathways and therapeutic targets for vascular malformations and to classify vascular malformations according to the molecular pathways involved. A literature review was performed using Embase and Medline. Different MeSH terms were combined for the search strategy, with the aim of encompassing all studies describing the classification, pathogenesis, and treatment of vascular malformations. Major pathways involved in the pathogenesis of vascular malformations are vascular endothelial growth factor (VEGF), Ras/Raf/MEK/ERK, angiopoietin-TIE2, transforming growth factor beta (TGF-β), and PI3K/AKT/mTOR. These pathways are involved in controlling cellular growth, apoptosis, differentiation, and proliferation, and play a central role in endothelial cell signaling and angiogenesis. Many vascular malformations share similar aberrant molecular signaling pathways with cancers and inflammatory disorders. Therefore, selective anticancer agents and immunosuppressants may be beneficial in treating vascular malformations of specific mutations. The current classification systems of vascular malformations, including the International Society of the Study of Vascular Anomalies (ISSVA) classification, are primarily observational and clinical, and are not based on the molecular pathways involved in the pathogenesis of the condition. Several molecular pathways with potential therapeutic targets have been demonstrated to contribute to the development of various vascular anomalies. Classifying vascular malformations based on their molecular pathogenesis may improve treatment by determining the underlying nature of the condition and their potential therapeutic target.